“We Use English But Not Like All the Time Like”—Discourse Marker Like in UAE English - Lorenz, Eliane (Frontiers in Communication, 2022)
The United Arab Emirates (UAE) is characterized by extensive language contact. Although Arabic is the official language, practically all communication in general as well as in higher education, in particular, takes place in English. The current study reports from the larger project Language, Attitudes, and Repertoires in the Emirates (LARES, 2019–2021) and investigates the use of English as a lingua franca (ELF) among university students in Sharjah, one of the seven sovereign emirates of the UAE. A spoken corpus based on 58 semi-structured interviews is used to examine the use of the discourse marker like. It has been shown to be a ubiquitous feature of English no longer confined to American English and occurs frequently in the corpus. It doubtlessly is a prominent discourse marker in the type of English spoken among the heterogeneous group of multicultural university students considered here. Although a large individual variation with respect to normalized frequencies of like can be observed, none of the social variables (i.e., gender, citizenship, L1, year of birth, number of languages, college, self-assessed proficiency in English, and English usage score) included in the analysis account for this variability. Instead, I argue that like as a discourse marker is part of the English repertoire of all students and appears to be even more frequently used than in other English varieties. This supports previous research arguing for an intensification of language change in ELF contexts as well as high individual variation as a characteristic of multilingual ELF users.